Carbon sequestration through hydrothermal carbonization of expired fresh milk and its application in supercapacitor. (December 2020) - Dat, Nguyen Tien; Tran, Thi Tuong Vi; Van, Cuong Nguyen; Vo, Dai-Viet N.; Kongparakul, Suwadee; Zhang, Haibo; Guan, Guoqing; Samart, Chanatip
Abstract: This study investigated the production of natural nitrogen-doped carbon from expired fresh milk for use in a supercapacitor electrode. The material was prepared by hydrothermal carbonization followed by sequential KOH–H3 PO4 activation. Carbon modified with KOH at a ratio of 1:1 had the largest Brunauer-Emmett-Teller surface area of 465 m 2 /g. Furthermore, the presence of surface functional groups played an important role in determining the specific capacitance. The highest specific capacitance of 186.3 F/g was obtained from carbon modified with C:KOH at 1:1 and 50 wt% H3 PO4 . An electrochemical impedance study suggested that charge storage resembled a modified Randles circuit. Carbon derived from expired milk and exposed to sequential KOH and H3 PO4 modification was shown to be a promising candidate material for use as electrodes in electric double-layer supercapacitors, while simultaneously reducing food waste. Graphical abstract: Image 1 Highlights: Carbon from expired fresh milk can be used in a supercapacitor electrode. The specific capacitance was higher than carbon derived from other forms of waste. Specific capacitance was affected by surface area and surface functional groups. Natural doped heteroatoms played a key role in improving capacitance. Specific capacitance (186.3 F/g) was higher than that of carbon from other waste.